Factors Influencing Muzakki's Interest To Pay Zakat In Yatim Mandiri Indonesia - Hidayat, Ahmad Agus; Sahdani, Heru; Hardiyanti, Istiqom Shinta; Novita, Siska Arie (LPPM ISNJ Bengkalis, 2024)
The research aims to examine the influence of institutional image, religiosity, transparency, and trust on the interest of muzakki in paying zakat at Yatim Mandiri. This study employs a quantitative method with data analysis techniques using a structural equation model (SEM). The research population consists of muzakki from Yatim Mandiri zakat institution in Ponorogo. The sampling technique used is random sampling with the Slovin approach, and the sample size is 164 muzakki. The sources include primary data from questionnaires distributed to muzakki at Yatim Mandiri. The research findings indicate that transparency, religiosity, and trust positively and significantly influence interest, while institutional image negatively and significantly influences interest. Trust is the most dominant factor influencing the interest of muzakki in paying zakat. This research can complement existing theories. Practically, this research can provide an understanding of muzakki in paying zakat. Then, it can become a reference for Yatim Mandiri in maintaining the institution's image, showing a sincere work ethic through transparency, and showing the trust of muzakki so that they can commit to paying zakat.